Subliminal and supraliminal processing of reward-related stimuli in anorexia nervosa. Issue 5 (23rd August 2017) - Boehm, I.; King, J. A.; Bernardoni, F.; Geisler, D.; Seidel, M.; Ritschel, F.; Goschke, T.; Haynes, J.-D.; Roessner, V.; Ehrlich, S.
Abstract : Background: Previous studies have highlighted the role of the brain reward and cognitive control systems in the etiology of anorexia nervosa (AN). In an attempt to disentangle the relative contribution of these systems to the disorder, we used functional magnetic resonance imaging (fMRI) to investigate hemodynamic responses to reward-related stimuli presented both subliminally and supraliminally in acutely underweight AN patients and age-matched healthy controls (HC). Methods: fMRI data were collected from a total of 35 AN patients and 35 HC, while they passively viewed subliminally and supraliminally presented streams of food, positive social, and neutral stimuli. Activation patterns of the group × stimulation condition × stimulus type interaction were interrogated to investigate potential group differences in processing different stimulus types under the two stimulation conditions. Moreover, changes in functional connectivity were investigated using generalized psychophysiological interaction analysis. Results: AN patients showed a generally increased response to supraliminally presented stimuli in the inferior frontal junction (IFJ), but no alterations within the reward system. Increased activation during supraliminal stimulation with food stimuli was observed in the AN group in visual regions including superior occipital gyrus and the fusiform gyrus/parahippocampal gyrus. No group difference was found with respect to the subliminal stimulation condition and functional connectivity. Conclusion: Increased IFJ activation in AN during supraliminal stimulation may indicate hyperactive cognitive control, which resonates with clinical presentation of excessive self-control in AN patients. Increased activation to food stimuli in visual regions may be interpreted in light of an attentional food bias in AN.